On‐Site Quantification and Infection Risk Assessment of Airborne SARS‐CoV‐2 Virus Via a Nanoplasmonic Bioaerosol Sensing System in Healthcare Settings. Issue 35 (30th October 2022) - Qiu, Guangyu; Spillmann, Martin; Tang, Jiukai; Zhao, Yi‐Bo; Tao, Yile; Zhang, Xiaole; Geschwindner, Heike; Saleh, Lanja; Zingg, Walter; Wang, Jing
Abstract: On‐site quantification and early‐stage infection risk assessment of airborne severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) with high spatiotemporal resolution is a promising approach for mitigating the spread of coronavirus disease 2019 (COVID‐19) pandemic and informing life‐saving decisions. Here, a condensation (hygroscopic growth)‐assisted bioaerosol collection and plasmonic photothermal sensing (CAPS) system for on‐site quantitative risk analysis of SARS‐CoV‐2 virus‐laden aerosols is presented. The CAPS system provided rapid thermoplasmonic biosensing results after an aerosol‐to‐hydrosol sampling process in COVID‐19‐related environments including a hospital and a nursing home. The detection limit reached 0.25 copies/µL in the complex aerosol background without further purification. More importantly, the CAPS system enabled direct measurement of the SARS‐CoV‐2 virus exposures with high spatiotemporal resolution. Measurement and feedback of the results to healthcare workers and patients via a QR‐code are completed within two hours. Based on a dose‐response µ model, it is used the plasmonic biosensing signal to calculate probabilities of SARS‐CoV‐2 infection risk and estimate maximum exposure durations to an acceptable risk threshold in different environmental settings. Abstract : A condensation‐assisted bioaerosol collection and plasmonic photothermal sensing (CAPS) system is presented for on‐site airborne SARS‐CoV‐2 virus detection and early‐stage infection risk assessment with high spatiotemporal resolution. The interpreted biosensing results can be used to assess the individual infection risk of susceptible persons (e.g., healthcare workers), as well as to predict the maximum acceptable exposure duration.